AAC technologies to enhance participation and access to meaningful societal roles for adolescents and adults with developmental disabilities who require AAC. - Mcnaughton D; Bryen DN (AAC: Augmentative & Alternative Communication, 2007)
In this paper we review published research describing the use of augmentative and alternative communication (AAC) to support societal participation by adolescents and adults with developmental disabilities who require AAC. We focus on three major participation domains: post-secondary education and training, the workplace, and community living and social interaction opportunities. Based on the findings of the review, we highlight five needed areas of research and development related to AAC technology: face to face communication; distance communication and interconnectivity; training and support for system use; adapted applications and cognitive tools; and supports for independent operation, development, and maintenance.